KAJI EKSPERIMENTAL SISTEM DESTILASI ASAP PEMBAKARAN SAMPAH PLASTIK MENJADI BAHAN BAKAR ALTERNATIF DENGAN PENDINGINAN SISTEM REFRIGERASI KOMPRESI UAP - Arda Rahardja Lukitobudi; Sugiyarto; Muhammad Setya Ramadhan; Dinda Ainun Qolbi (KURVATEK, 2020)
One step to reduce plastic waste and at the same time to produce alternative fuel is by pyrolysis of smoke destilation of plastic waste burning result because basically the material of plastic waste is hydrocarbon. This research will be discussed about experimaental study of smoke destilator machine of plastic waste burning result using vapor compression refrigeration system in various temperature without analizing the economical factor. There was two step destilation done, using local temperature air and by refrigerated heat exchanger using 35% propylene glycol as secondary refrigerant and with R134A as the primary refrigerant. In destilation step using secondary refrigerant was done by baffled counter flow tube in tube heat exchanger in order to obtain turbulent flow and was done in various temperature that was local temperature air and temperature under 10℃: 9℃, 3℃ and -3℃. The plastic waste which was burnt is 2 kg Low Density PolyEthylene LDPE using reactor with L:40cm x W:40cm x H:60cm and 3 kg elpiji gas burner in temperature of ±400°C. The design was assumed to maximize plastic waste burnt result smoke destilation process. The lower destilation temperature generate the higher alternative fuel volume. During ±4 hours measurement, with temperature of 9℃ generates 480 mL fuel, while 3℃ generates 615 mL fuel, -3℃ generates 710 mL fuel and with local temperature destilation only generates 390 mL fuel.